Buccinator-based myomucosal flaps in intraoral reconstruction: A review and new classification - Rahpeyma, Amin (Medknow Publications & Media Pvt Ltd, 2013)
The buccinator-based myomucosal flaps are axial pattern flaps that are suitable in reconstruction of medium sized oral soft tissue defects; they are rich in blood supply, have appropriate thickness and considerable mucosal paddle, and they can secrete saliva. The present study describes surgical anatomy and blood supply of these flaps and demonstrates all possible modifications of these flaps (9 modifications). Many terms (> 10) have been used to refer to buccinator-based myomucosal flaps in the literatures. This report introduces a new classification system mainly based on the remaining attachments of buccinator muscle after flap elevation in pedicle variants and axial blood supply orientation in island variants.